2021
DOI: 10.1039/d1tc01691a
|View full text |Cite
|
Sign up to set email alerts
|

Highly self-healable and recyclable graphene nanocomposites composed of a Diels–Alder crosslinking/P3HT nanofibrils dual-network for electromagnetic interference shielding

Abstract: In this study, a novel self-healing material with a dual-network composed of cross-linked structure by Diels–Alder (DA) chemistry interconnected with self-assembled π-conjugated polymer nanofibrils was developed for application in electromagnetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Even so, the mechanical properties of the composite films are still favorable for the practical applications. In terms of Figure b, our prepared PPPg delivers superior mechanical behavior, as compared to previous works, regarding the maximum stress and the corresponding tensile elastic strain, such as EMIM-TFSI (5 MPa, 31%), CNC/MXene (1.025 MPa, 675%), T 6 PAM (0.819 MPa, 80%), PG5H10 (2.6 MPa, 12%), Fe 3 O 4 /PEDOT: PSS/PVA (0.55 MPa, 850%), RGO-Ga (0.06 MPa, 70%) and PVA/MXene (0.6 MPa, 80%) . After more than 20 times bending and folding, it can be observed that the prepared PPPg-20 still possesses great flexibility (Figure c,d).…”
Section: Resultsmentioning
confidence: 56%
“…Even so, the mechanical properties of the composite films are still favorable for the practical applications. In terms of Figure b, our prepared PPPg delivers superior mechanical behavior, as compared to previous works, regarding the maximum stress and the corresponding tensile elastic strain, such as EMIM-TFSI (5 MPa, 31%), CNC/MXene (1.025 MPa, 675%), T 6 PAM (0.819 MPa, 80%), PG5H10 (2.6 MPa, 12%), Fe 3 O 4 /PEDOT: PSS/PVA (0.55 MPa, 850%), RGO-Ga (0.06 MPa, 70%) and PVA/MXene (0.6 MPa, 80%) . After more than 20 times bending and folding, it can be observed that the prepared PPPg-20 still possesses great flexibility (Figure c,d).…”
Section: Resultsmentioning
confidence: 56%
“…This not only hampers the formation of an EMI shielding conductive network but also adversely affects the mechanical strength and self-healing effect of the composite material. To address this issue, Lee et al 110 developed a novel self-healing EMI shielding material. This material was created by incorporating graphene This journal is © The Royal Society of Chemistry 2024 nanosheets (GNS) into a complex copolymer.…”
Section: Intrinsically Conducting Polymer (Icp) Systemsmentioning
confidence: 99%
“…To overcome the drawbacks of metal shielding systems, researchers have developed alternative systems. Composite materials composed of a polymeric matrix and conductive fillers, such as carbon fibers, 29,30 carbon black, 31,32 graphene, 33,34 and carbon nanotubes, have been developed for this purpose. 35,36 Composite materials based on carbon allotropes are cheaper, lighter, easier to be processed, and more environmentally stable than metals.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the drawbacks of metal shielding systems, researchers have developed alternative systems. Composite materials composed of a polymeric matrix and conductive fillers, such as carbon fibers, , carbon black, , graphene, , and carbon nanotubes, have been developed for this purpose. , Composite materials based on carbon allotropes are cheaper, lighter, easier to be processed, and more environmentally stable than metals. EMI shielding composites involving micropores formation through sc-CO 2 foaming have recently been developed. These hole-type systems have a microcellular structure, which not only provides them with the advantage of being lightweight but also promotes the arrangement of fillers around cells and mediates multiple reflections of electromagnetic waves within the systems, thereby synergistically enhancing the absorption efficiency of the systems for electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%